Ortodocși și greco-catolici în Banat (a doua jumătate a secolului al XIX-lea și începutul secolului XX). Perspectiva lui Ioan Boroș / Orthodox and Greek Catholics in Banat (second half of the 19th and early 20th century). The perspective of Ioan Boroș - Ion Carja (Analele Banatului. Arheologie-Istorie, 2021)
Bringing back into actuality a personality as important as Ioan Boroș (1850-1937), a reference figure of the Banat Greek Catholicism during the second half of the 19th century and the first decades of the next, represents a significant acquisition, an important result of the research efforts that were conducted after 1989 in the area of church history. In this respect, two major historiographical restitutions must be mentioned; after they saw the light of the printing press, they contributed in a the decisive manner in placing in the spotlight the proposed archiereus Ioan Boroș to the Romanian historiography and to the contemporary Greek-Catholic ecclesial and community consciousness; it is the publication of his memorial notes, along with his will, correspondence and documents proving his elevation to the rank of honorary archiereus, in the period immediately following the Great Union. A first book containing his historical writings is of great importance in understanding his intellectual profile and the great diversity of the concerns that animated him. Considering the intellectual formation, the life experience and the exceptional church administrative skill that Ioan Boroș showed, we consider that it is not without interest to see how his memorial notes and, on a broader level, his scientific and publishing activity, reflect the multi-confessional character of Banat and especially the relations between the two Romanian confessions, Orthodoxy and Greek Catholicism. This is the aim of the present research paper.